PENGGUNAAN METODE DEMONSTRASI DALAM PEMBELAJARAN MUSIK DAERAH SETEMPAT (MINANGKABAU) DI KELAS X IPA 1 SMA N 1 BUKITTINGGI - Vinny Aprilina; Irdhan Epria Darma Putra; Yos Sudarman (SENDRATASIK UNP, 2018)
AbstractThis article was aimed to find out 1)how to use demonstration methodin local music learning especially talempong in class X IPA SMAN 1 Bukittinggi, 2)  how students' ability in playing talempong with the right tempo and tone. Type of the research was qualitative. The source of data were divided into two, they were primary and secondary. Technique of data collection was done by using some methods by taking observation, interview and documentation. Technique of data analysis was carried out based on Miles and Huberman’s theory namely data reduction, presentation and verification. Result of the research showed that the use of demonstration method used by teachers was appropiate as it should be, i.e. teachers gave example and guided the students well, it meant that the method has already worked. For the Students' ability in playing talempong, there were 19 students got 90 (52.8%), and 17 of students got 60 (47.2%). So it could be said that only 19 of students were able to play talempong withgood and right. Keywords: Usage, Demonstration Method, Local Music Learning (Minangkabau)